METHODOLOGY FOR USING AUTHENTIC MATERIALS IN THE DEVELOPMENT OF COGNITIVE-PRAGMATIC COMPETENCE (SCIENCE TIME JOURNAL, 2026)
This article analyzes the theoretical and practical aspects of using authentic materials in developing cognitive-pragmatic competence. The study highlights the role of authentic texts, audio and video materials, podcasts, and interviews in fostering students’ understanding of pragmatic content, understanding of communicative intentions, and developing contextual communication skills. The effectiveness of discourse analysis, role-playing, and case-study methods in developing cognitive-pragmatic competence is also substantiated. The research results demonstrate that the use of authentic materials serves to increase the effectiveness of foreign language education and enhance students’ communicative readiness.